Ethics in Neuromarketing and its Implications on Business to Stay Vigilant - Mohd Isa, Salmi; Azlina Mansor, Aida; Razali, Khairiah (KnE Social Sciences, 2019)
Neuromarketing is an emerging field in which academic and industry research employ neuroscience techniques to understand the consumers’ mind by explaining consumers’ preferences, motivations, and expectations. Nevertheless, some people claimed that the use of neuroscience in marketing somehow had introduced companies to a ‘buy button’ that can read the mind of potential consumers and influence their buying decisions. Plus, those that oppose neuromarketing also believe that the act of ‘reading’ consumers’ mind with the aim of improving company services is unethical and should not be used, let alone implied. However, what does actually ‘ethics in neuromarketing’ means in the first place? Moreover, how does this become an issue in the marketing field? Herein, we will articulate common ethical concerns with neuromarketing. We argue that the most frequently raised concerns- autonomy, informed consent, confidentiality, privacy, benevolence, and no maleficence-given the current capabilities for business to stay vigilant. However, we identify how potentially serious ethical issues may emerge from neuromarketing practices in the industry, which are primarily exclusive. We identify approaches that business can use and reduce the threats to consumers. We conclude that neuromarketing has clear potential for business to stay vigilant and mitigate the positive impact on society.